2016
DOI: 10.1111/resp.12919
|View full text |Cite
|
Sign up to set email alerts
|

Do inhaled corticosteroids protect against lung cancer in patients with COPD? A systematic review

Abstract: Inhaled corticosteroids (ICS) are commonly prescribed to COPD patients, particularly those with more advanced stages of the disease. These patients are also at increased risk of lung cancer. A systematic review was undertaken to identify studies that examined the association between lung cancer risk and ICS therapy in COPD patients. The search strategy was created in MEDLINE and extended to EMBASE as well as other relevant databases. Both randomized controlled trials (RCTs) and observational studies were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Inhaled corticosteroids (ICS), which are commonly prescribed to COPD patients, are now showing a potential cancer prevention effect [31]. A nested case-control study of patients with COPD demonstrated that regular use of ICS was significantly associated with a decreased lung cancer risk [32].…”
Section: Lung Cancer Prevention In Copd Patientsmentioning
confidence: 99%
“…Inhaled corticosteroids (ICS), which are commonly prescribed to COPD patients, are now showing a potential cancer prevention effect [31]. A nested case-control study of patients with COPD demonstrated that regular use of ICS was significantly associated with a decreased lung cancer risk [32].…”
Section: Lung Cancer Prevention In Copd Patientsmentioning
confidence: 99%
“…Their analysis of randomized controlled trials (RCTs) showed no statistically significant association between ICS use and lung cancer risk, whereas observational studies showed a protective effect of ICS use, particularly at higher doses and with more frequent use [27]. The primary objective of these RCTs was not to examine the protective effects of ICS on lung cancer, but the efficacy of ICS use in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective observational study demonstrated that a high ICS dose is correlated with a decreased risk of lung cancer [20]. However, there are many conflicting ideas in the literature about the role of ICS in the prevention of lung cancer [2027]. Taiwan's National Health Insurance (NHI) database may provide a larger population and longer follow-up interval data than previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is also advocated by the GOLD 2017 report and discussed in an editorial by Calverley . A systematic review of the impact of inhaled corticosteroid treatment on the risk of lung cancer in COPD by Raymakers et al . found that randomized studies demonstrated no evidence of benefit, although descriptive studies showed some protection at high doses.…”
Section: Copdmentioning
confidence: 99%
“…This approach is also advocated by the GOLD 2017 report and discussed in an editorial by Calverley. 16,31 A systematic review of the impact of inhaled corticosteroid treatment on the risk of lung cancer in COPD by Raymakers et al 32 found that randomized studies demonstrated no evidence of benefit, although descriptive studies showed some protection at high doses. Finally, a prospective cohort study by Shin et al 4 reported post-operative respiratory complications in nearly 25% of COPD patients following extra-pulmonary surgery.…”
Section: Pharmacological Managementmentioning
confidence: 99%